Analysis of the drying kinetics of S. Bartolomeu pears for different drying systems. - Guiné, Raquel (2013)
Pears of the variety S. Bartolomeu (Pyrus communis L.) are used in Portugal to produce a traditional food product, which is obtained by open-air sun drying. The traditional processing has many disadvantages, namely the efficiency and the sanitary quality of the final product. For these reasons, attempts have been made to study alternative production methodologies, including the use of a solar stove, a solar drier and a drying tunnel. In the present work pears of the variety S. Bartolomeu, were dried in the three alternative systems mentioned, and their drying kinetics was studied over a three year period of study. Eight different models from literature were tested and their performance was evaluated in terms of some statistical indicators. From the results obtained it was possible to conclude that the equations used to describe the drying kinetics that best fit the experimental data were Henderson & Pabis, Logarithmic and Vega-Lemus. Furthermore, it was concluded that the solar drying was very dependent on the weather conditions, varying the drying time in the experiments carried out in the three years of study. It was also possible to observe that the loss of water was much more uniform in the drying tunnel system when compared to the solar dryings, because in the tunnel the operating temperature and air velocity were constant.